2022
DOI: 10.3389/fmicb.2022.935193
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanotechnology as a Potential Alternative for Plant Viral Disease Management

Abstract: Plant viruses cause enormous losses in agricultural production accounting for about 47% of the total overall crop losses caused by plant pathogens. More than 50% of the emerging plant diseases are reported to be caused by viruses, which are inevitable or unmanageable. Therefore, it is essential to devise novel and effective management strategies to combat the losses caused by the plant virus in economically important crops. Nanotechnology presents a new tendency against the increasing challenges in the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 88 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…This result was an agreement with that of [34], which reported that the nanoparticles, especially those synthesized by B. licheniformis, showed excellent in vitro antiviral activity against the bean yellow mosaic virus. The significance of the particular antiviral activity is highlighted, given the significant yield reduction in fava bean crops resulting from bean yellow mosaic virus infections in many African countries [37][38][39][40]. This study indicates the ability of silver nanoparticles to prevent the release of viral RNA from the protein coat of the virus.…”
Section: Activity Of Agnps Against Pmmovmentioning
confidence: 90%
“…This result was an agreement with that of [34], which reported that the nanoparticles, especially those synthesized by B. licheniformis, showed excellent in vitro antiviral activity against the bean yellow mosaic virus. The significance of the particular antiviral activity is highlighted, given the significant yield reduction in fava bean crops resulting from bean yellow mosaic virus infections in many African countries [37][38][39][40]. This study indicates the ability of silver nanoparticles to prevent the release of viral RNA from the protein coat of the virus.…”
Section: Activity Of Agnps Against Pmmovmentioning
confidence: 90%
“…These include the use of plant material that is resistant and/or tolerant to these viruses, in addition to the use of virus-free material combined with cultural practices, such as weed control and crop rotation, as well as controlling vector-mediated transmission. These control options have been comprehensively described by other reviews [ 3 , 13 , 36 , 132 , 133 , 134 , 135 , 136 , 137 ], and even novel techniques based on nanotechnology have been recently reported for the management of plant virus diseases [ 138 , 139 , 140 ]. In cucurbit crops, it is important to consider that these crops grow in open fields and temperate growing areas, where the aphid-vector populations are also major pests that are difficult to control.…”
Section: Overview Of the Management Of Aphid-transmitted Viral Diseasesmentioning
confidence: 99%
“…Nanomaterials 1−100 nm in size hold more than enough potentiality, and based on today's scenarios, researchers are highly interested in studying them because of their stability, specificity, reactivity, shape, size, and many more properties. 12 Silver, gold, copper, zinc, and titanium nanoparticles can be synthesized as nanopesticides to destroy plant-affecting insects and, therefore, are widely applied for plant disease resistance. To construct such a nanopesticide, the insoluble active ingredient is fused with the inorganic coating of nanoparticles or conjugated with the polymers.…”
Section: Nanomaterial-based Rnai Delivery For Pest and Crop Managementmentioning
confidence: 99%
“…17 Per studies, it was observed that the nanocarrier mode of the RNAi gene dysregulating method to prevent pests and microbes like the African malaria mosquito, yellow fever mosquito, bean yellow mosaic virus, cucumber mosaic virus, Rhizoctonia solani, Fusarium oxysporum, Xanthomonas oryzae, and so on is a successful utilization. 12,18,19 The tomato leaf miner is another disease-causing insect, which can be decreased using nanobioconjugates as a remedy for the ailment. 20 3.1.…”
Section: Nanomaterial-based Rnai Delivery For Pest and Crop Managementmentioning
confidence: 99%